VIM : the magazine for vigorous living. (Chicago : Victory Printing and Publishing Co., 1955)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Victory Printing and Publishing Co. 179 West Washington Street, Chicago 2 ; vanaf vol 7 n° 9 : Nirvack Publishers Inc., Box 9300 Chicago 90
Engels
Periodiek